Towards a framework for gamified programming education - Swacha, Jakub (2019)
Computer programming is a difficult subject that can only be mastered with lots of practice. It is therefore of primary importance to rise and retain students' engagement during a programming course, a task in which gamification has been proven as a competent method. Even though there are numerous reports on applying gamification to programming courses, there are no available open resources or dedicated platforms that could be used by programming teachers to gamify their courses, meeting both the requirements of being easy to adopt and leaving the decisions on the scope of the course and the level of gamification to the teachers themselves. In order to fulfill this gap, a consortium of four European institutions initiated a common project to develop open gamified programming exercises and interactive course materials for popular programming languages. In this paper, we report the results of the first stage of this work, which defined the range of gamification concepts to be covered within the developed framework and its evaluation by students.